Determination of fibrin clot growth and spatial thrombin propagation in the presence of different types of phospholipid surfaces. (17th November 2021) - Koltsova, Ekaterina M.; Kuprash, Anna D.; Dashkevich, Natalya M.; Vardanyan, David M.; Chernyakov, Artem V.; Kumskova, Maria A.; Nair, Sukesh C.; Srivastava, Alok; Ataullakhanov, Fazoil I.; Panteleev, Mikhail A.; Balandina, Anna N.
Abstract: In this work, we present a new method—Thrombodynamics-4D—for the assessment of both plasma and platelet contributions to clotting. Thrombodynamics-4D potentially allows for the determination of plasma or platelet disorders and the effects of various drugs on plasma clotting or on platelet procoagulant function. In this assay, clot formation in platelet-rich plasma or platelet-free plasma supplemented with phospholipids is activated with tissue factor immobilized on a surface. Spatial fibrin clot growth and thrombin concentration dynamics are registered by measuring light scattering of the fibrin clot and fluorescence of the product formed by cleavage of the synthetic fluorogenic substrate by thrombin, respectively. Here, we describe the preanalytical requirements, measurement methodology and calculation principles of assay parameters. Preanalytical and analytical variability and reference ranges of the assay are given. Additionally, we show some clinical examples, which determine the effect of anticoagulants, measure clotting dysfunction in patients with platelet or coagulation disorders and evaluate the effect of surgery.